Usability of cellulose-based binder in water-based flexographic ink - SÖNMEZ, SİNAN (My University, 2022)
Packaging must have a good commercial appearance and is generally obtained by ink transferred to its substrate. It is important that the ink used in packaging printing is produced from environmentally friendly and sustainable raw materials as well as being suitable for the printing system. The increasing demand in the field of printed packaging and the scarcity of resources to meet this demand have accelerated the search for new sources for inks. For this purpose, inks produced in the laboratory using a modified cellulose-based binder, a commercial acrylic resin and a commercial soybean protein were compared with a commercial ink. As a result of the study, it was determined that the printability properties of the ink obtained by using the modified cellulose-based binder were better than the ink obtained with commercial soybean protein. It was determined that it showed printability properties close to the ink produced with commercial acrylic binders. By using modified cellulose-based water-based flexographic ink instead of other commonly used binders, more environmentally friendly sustainable inks can be produced.
Keywords: Kimya Mühendisliği ve Teknolojisi; Tekstil Mühendisliği ve Teknolojisi; Kimya; Diğer; Temel Bilimler; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Textile Engineering and Technology; Chemistry; Other; Natural Sciences; Engineering and Technology; KİMYA, UYGULAMALI; Temel Bilimler (SCI); MÜHENDİSLİK, KİMYASAL; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); MALZEME BİLİMİ, TEKSTİL; Malzeme Bilimi; CHEMISTRY, APPLIED; CHEMISTRY; Natural Sciences (SCI); ENGINEERING, CHEMICAL; ENGINEERING; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE, TEXTILES; MATERIALS SCIENCE; Genel Malzeme Bilimi; Genel Mühendislik; Mühendislik (çeşitli); Kimya (çeşitli); Genel Kimya; Proses Kimyası ve Teknolojisi; Akışkan Akışı ve Transfer İşlemleri; Kolloid ve Yüzey Kimyası; Kimyasal Sağlık ve Güvenlik; Kataliz; Kimya Mühendisliği (çeşitli); Genel Kimya Mühendisliği; Fizik Bilimleri; General Materials Science; General Engineering; Engineering (miscellaneous); Chemistry (miscellaneous); General Chemistry; Process Chemistry and Technology; Fluid Flow and Transfer Processes; Colloid and Surface Chemistry; Chemical Health and Safety; Catalysis; Chemical Engineering (miscellaneous); General Chemical Engineering; Physical Sciences